2022
DOI: 10.2147/dmso.s369712
|View full text |Cite
|
Sign up to set email alerts
|

Potential Effect of DPP-4 Inhibitors Towards Hepatic Diseases and Associated Glucose Intolerance

Abstract: Dipeptidyl-peptidase-4 (DPP-4) is an enzyme having various properties and physiological roles in lipid accumulation, resistance to anticancer agents, and immune stimulation. DPP-4 includes membrane-bound peptidases and is a kind of enzyme that cleaves alanine or proline-containing peptides such as incretins, chemokines, and appetite-suppressing hormones (neuropeptide) at their N-terminal dipeptides. DPP-4 plays a role in the final breakdown of peptides produced by other endo and exo-peptidases from nutritious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 182 publications
0
4
0
Order By: Relevance
“…27 Research has suggested that DPP-4 inhibitors could have therapeutic implications in NAFLD due to their influence on hepatic lipid metabolism and their inherent anti-inflammatory attributes. 28 In preclinical models, Evogliptin has demonstrated notable benefits by mitigating hepatic steatosis, inflammation, and fibrosis. 29 One trial incorporated Evogliptin to evaluate its efficacy and safety for T2DM patients concurrently diagnosed with NAFLD.…”
Section: Resultsmentioning
confidence: 99%
“…27 Research has suggested that DPP-4 inhibitors could have therapeutic implications in NAFLD due to their influence on hepatic lipid metabolism and their inherent anti-inflammatory attributes. 28 In preclinical models, Evogliptin has demonstrated notable benefits by mitigating hepatic steatosis, inflammation, and fibrosis. 29 One trial incorporated Evogliptin to evaluate its efficacy and safety for T2DM patients concurrently diagnosed with NAFLD.…”
Section: Resultsmentioning
confidence: 99%
“…In this overview, we will explore the emerging therapeutic potential of CBD in neurological disorders [22]. CBD has been found to interact with the body's endocannabinoid system (ECS) [23], which is involved in regulating various physiological processes, including pain sensation, mood, appetite, and immune function [24]. CBD's interaction with the ECS has been shown to have anti-inflammatory, neuroprotective, and antioxidant effects, which could be beneficial in treating neurological disorders [25].…”
Section: Cannabidiol (Cbd): An Overviewmentioning
confidence: 99%
“…Diferent plant tissues contain favonoids either internally or externally [8]. Te pharmaceutical and biological ascribe to favonoids such as antimalarial, cytotoxic, anticancer, cardioprotective, hepatoprotective, antileishmanial, antitrypanosomal, antiinfammatory, and neuroprotective antiamoebic and also efective in the therapy of age-related factors, diabetes, and Alzheimer's disease [8,9]. Tese qualities are typically attributed to their capacity for metal chelation, activity in scavenging free radicals, and degree of specifcity in protein binding ability.…”
Section: Chemical Structure Of Flavonoids and Their Subclassesmentioning
confidence: 99%